Relationship between Parental Social Control with Deviant Behavior Early Childhood - Nadya Ullil Azmi; Ismaniar Ismaniar; Syuraini Syuraini (Universitas Negeri Padang, 2019)
This research is background many problems of early childhood deviant behavior in Jorong Koto Nagari Aie Dingin Kecamatan Gumanti valley district Solok district. This is alleged lack of social control of parent to behavior of early child in Jorong Koto Nagari Aie Dingin Kecamatan Gumanti valley district Solok district. This study aims to look at the picture of parental social control and behavior of deviant early childhood in Jorong Koto Nagari Aie Dingin Kecamatan Gumanti valley district Solok district. This research was quantitative correlation type with using propotional random sampling. The data collection technique was a questionnaire and the data collection toll in the form of sheet statement. Data analysis tecniques using the formula persentages and product moment. The Reserch found that (1) the social control of parents in Jorong Koto Jorong Koto Nagari Aie Dingin Kecamatan Gumanti valley district Solok district still low, (2) deviant behavior of children early age is encourage in Jorong Koto Nagari Aie Dingin Kecamatan Gumanti valley district Solok district relatively high, (3) there is a significant relationship between the social control of parents with early childhood deviant behavior Jorong Koto Nagari Aie Dingin Kecamatan Gumanti valley district Solok district.Keywords: Parental Social Control, Deviant Behaviour, Early Childhood